2009
DOI: 10.1177/0258042x0903400406
|View full text |Cite
|
Sign up to set email alerts
|

Mathematics Anxiety, Mathematics Performance and Overall Academic Performance in High School Students

Abstract: This paper examined the relationship between Mathematics anxiety, Mathematics performances and overall academic performance in high school students. 424 (111 males and 113 females) of high school students from three states in South India, responded to a Mathematics Anxiety Scale and Socio Demographic Questionnaire. The effects of gender on Mathematics anxiety, Mathematics performance and overall academic performance were examined and after data collection Pearson Correlation Analysis and two Independent Sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 7 publications
(2 reference statements)
2
6
1
Order By: Relevance
“…This may be that subjects such as geometry in mathematics get more challenging for female students than male students, and as they progress to the next level, the female students either repeat or stop schooling due to failure in mathematics due to fear for geometry. This finding is with the findings of Karimi and Venkatesan (2017). They found out that geometry anxiety has a negative correlation with gender performance in mathematics.…”
Section: Discussionsupporting
confidence: 90%
“…This may be that subjects such as geometry in mathematics get more challenging for female students than male students, and as they progress to the next level, the female students either repeat or stop schooling due to failure in mathematics due to fear for geometry. This finding is with the findings of Karimi and Venkatesan (2017). They found out that geometry anxiety has a negative correlation with gender performance in mathematics.…”
Section: Discussionsupporting
confidence: 90%
“…The result of the study supported Seng's (2015) study, which also showed that there was a positive relationship between mathematics anxiety and numerical anxiety on students' mathematical performances. However, the result of the study contradicted Kangar et al (2010) and Karimi and Venkatesh (2010), where both studies showed a negative relationship between mathematics anxiety and mathematics performance.…”
Section: Discussion and Limitationscontrasting
confidence: 65%
“…Mathematics anxiety occurs within all levels of education and continues to rise as the year progresses (Yurtcu & Dogan, 2003). The level of mathematics anxiety in students can also be an honest indicator of students' academic success (Karimi & Venkatesh, 2010). A study by Sheffield and Hunt (2006) found that students with high mathematics anxiety levels generally performed low in their mathematics assessments.…”
Section: Introductionmentioning
confidence: 99%
“…Mathematics Anxiety Rating Scale-India (MARS-I): This questionnaire was developed by Karimi (2008); and contains 31 items of situations which causes mathematics anxiety. It has two subscales -Math test Anxiety with 15 items and Numerical tasks with 16 items .Each item of this scale was rated on a five -point scale rating , from very much anxious -5 to not at all anxious-1) .…”
Section: Tools and Materialsmentioning
confidence: 99%